THE IMPLEMENTATION OF COURSE REVIEW HORAY MODEL IN TIK SUBJECT TO IMPROVE THE LEARNING RESULTS OF CLASS X5 OF SMA NEGERI 2 SINGARAJA - Gde Ambara Putra (Universitas Pendidikan Ganesha, 2012)
This research was aimed at (1) improving the students’ learning results in TIK subject of class X5 SMA Negeri 2 Singaraja through the implementation of course review horay models (2) investigating the students’ response of class X5 SMA Negeri 2 Singaraja toward the implementation of course review horay models in TIK subject. The design of the research was a Classroom Action Research which consisted of two cycles. Each cycle consisted of four steps namely planning, action, observation and evaluation, and reflection. The subject of this research was the students of class X5 SMA Negeri 2 Singaraja in academic year 2011/2012. The class consisted of 35 students. Meanwhile, the objects of this research were (1) students’ learning results and (2) students’ response toward the implementation of course review horay models in TIK subject. The data of students’ learning results in TIK subject were collected through the test and observation, and the data of students’ response were collected through questionnaire. The collected data was analyzed by using descriptive analysis. Based on the analysis of data obtained, this research showed that the students’ learning results got improvement. Cycle I, the mean of students’ scores was 78,46 and the percentage of students’ classical success was 71,42%, as for cycle 2, the mean of students’ scores was 84,88 and the percentage of students’ classical success was 85,71%. The students’ responses toward the implementation of course review horay models in TIK subject come in positive category with a mean of 65.